Pengaruh Leverage, Earning Variability, Dan Dividend Payout Ratio Terhadap Beta Saham - Marhamah, Marhamah; Mursidah, Mursidah; Yunita, Nur Afni; Yunina, Yunina; Indrayani, Indrayani (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2023)
This study aims to examine the effect of leverage, earning variability, and dividend payout ratio on stock beta (study on companies listed on the Jakarta Islamic Index (JII) in 2018-2020). The sample in this study consisted of 15 companies listed on the Jakarta Islamic Index with data published on the Indonesian Stock Exchange. This study use panel data of 45 observations with panel data regression estimation with a fixed effect model assisted by the E-views 10 program. The results of the study found that leverage and dividend payout ratio variables have a positive effect on stock beta, while earning variability has a negative effect on stock beta